2020
DOI: 10.1016/j.phymed.2020.153296
|View full text |Cite
|
Sign up to set email alerts
|

Phillyrin (KD-1) exerts anti-viral and anti-inflammatory activities against novel coronavirus (SARS-CoV-2) and human coronavirus 229E (HCoV-229E) by suppressing the nuclear factor kappa B (NF-κB) signaling pathway

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has extensively and rapidly spread in the world, causing an outbreak of acute infectious pneumonia. However, no specific antiviral drugs or vaccines can be used. Phillyrin (KD-1), a representative ingredient of Forsythia suspensa, possesses anti-inflammatory, anti-oxidant, and antiviral activities. However, little is known about the antiviral abilities and mechanism of KD-1 against SARS-CoV-2 and human coronavirus 229E (HCoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 34 publications
0
60
0
Order By: Relevance
“…It's investigated that KD-1 could attenuate the inflammatory reaction and pathological changes caused by influenza A virus and LPS-infected mice ( Qu et al, 2016 ; Zhong et al, 2013 ). Furthermore, KD-1 could protect against SARS-CoV-2 and human coronavirus 229E attack via suppressing the activity of NF-кB signaling pathway ( Ma et al, 2020 ). A recent study revealed that CGA and KD-1 has an effective ability to prevent the combination of SARS-CoV-2-spike protein and ACE2 through the molecular docking method ( Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It's investigated that KD-1 could attenuate the inflammatory reaction and pathological changes caused by influenza A virus and LPS-infected mice ( Qu et al, 2016 ; Zhong et al, 2013 ). Furthermore, KD-1 could protect against SARS-CoV-2 and human coronavirus 229E attack via suppressing the activity of NF-кB signaling pathway ( Ma et al, 2020 ). A recent study revealed that CGA and KD-1 has an effective ability to prevent the combination of SARS-CoV-2-spike protein and ACE2 through the molecular docking method ( Yu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the SARS-CoV-2 virus was shown to use the NF-κβ pathway for the release of the pro-inflammatory cytokines such as TNFα and IL-6 ( Fig. 2 ) [ 64 ]. A previous study on SARS-CoV reported that S protein significantly increases NF-κβ activity and that the NF-κβ inhibition, leads to a strong inhibition of TNFα and IL-6 release [ 65 ].…”
Section: How Does Sars-cov-2 Initiate Cytokine Release and What Are Tmentioning
confidence: 99%
“…Likewise, phillyrin (KD-1), a representative constituent of Forsythia suspensa (Thunb. ), presented an EC50 at 63.90 μ g/mL and CC50 of 1959 μ g/mL [ 38 ]. Sulfated polysaccharides named RPI-27 and heparin inhibited SARS-CoV-2 in vitro with an EC50 of 8.3 ± 4.6 μ g/mL and 36 ± 14 μ g/mL, respectively [ 39 ].…”
Section: Discussionmentioning
confidence: 99%